Cellular and Molecular Phenotypes of pConsensus Peptide (pCons) Induced CD8+ and CD4+ Regulatory T Cells in Lupus - Ram P. Singh (Frontiers Media S.A., 2021)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with widespread inflammation, immune dysregulation, and is associated with the generation of destructive anti-DNA autoantibodies. We have shown previously the immune modulatory properties of pCons peptide in the induction of both CD4+ and CD8+ regulatory T cells which can in turn suppress development of the autoimmune disease in (NZB/NZW) F1 (BWF1) mice, an established model of lupus. In the present study, we add novel protein information and further demonstrate the molecular and cellular phenotypes of pCons-induced CD4+ and CD8+ Treg subsets. Flow cytometry analyses revealed that pCons induced CD8+ Treg cells with the following cell surface molecules: CD25highCD28high and low subsets (shown earlier), CD62Lhigh, CD122low, PD1low, CTLA4low, CCR7low and 41BBhigh. Quantitative real-time PCR (qRT-PCR) gene expression analyses revealed that pCons-induced CD8+ Treg cells downregulated the following several genes: Regulator of G protein signaling (RGS2), RGS16, RGS17, BAX, GPT2, PDE3b, GADD45β and programmed cell death 1 (PD1). Further, we confirmed the down regulation of these genes by Western blot analyses at the protein level. To our translational significance, we showed herein that pCons significantly increased the percentage of CD8+FoxP3+ T cells and further increased the mean fluorescence intensity (MFI) of FoxP3 when healthy peripheral blood mononuclear cells (PBMCs) are treated with pCons (10 μg/ml, for 24-48 hours). In addition, we found that pCons reduced apoptosis in CD4+ and CD8+ T cells and B220+ B cells of BWF1 lupus mice. These data suggest that pCons stimulates cellular, immunological, and molecular changes in regulatory T cells which in turn protect against SLE autoimmunity.